2006
DOI: 10.1534/genetics.106.056911
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Genomewide Rate of Adaptive Protein Evolution in Drosophila

Abstract: When polymorphism and divergence data are available for multiple loci, extended forms of the McDonald-Kreitman test can be used to estimate the average proportion of the amino acid divergence due to adaptive evolution-a statistic denoted a. But such tests are subject to many biases. Most serious is the possibility that high estimates of a reflect demographic changes rather than adaptive substitution. Testing for between-locus variation in a is one possible way of distinguishing between demography and selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
191
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(203 citation statements)
references
References 54 publications
11
191
1
Order By: Relevance
“…Last, we examined the 37 most abundant gene ontology categories in our data (58% and 38% of the exome data on the autosome and the X, respectively). We found a significant heterogeneity in α among categories on autosomes (Λ = 184, P < 1e-6) and on the X chromosome (Λ = 54, P < 0.003), suggesting that the differences above are genuine (6).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…Last, we examined the 37 most abundant gene ontology categories in our data (58% and 38% of the exome data on the autosome and the X, respectively). We found a significant heterogeneity in α among categories on autosomes (Λ = 184, P < 1e-6) and on the X chromosome (Λ = 54, P < 0.003), suggesting that the differences above are genuine (6).…”
Section: Resultsmentioning
confidence: 78%
“…This allows measurement of the amount of adaptive evolution on the branch leading to chimpanzees, using the approach of ref. 6. All autosomes have an excess of nonsynonymous polymorphisms segregating compared with nonsynonymous fixed differences, leading to a neutrality index (NI) >1 and no evidence for adaptive evolution (Table S8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has suggested that a substantial fraction of nonsynonymous substitutions in Drosophila were fixed through positive selection [81][82][83][84][85] . We estimate that 33.1% of single-copy orthologues in the melanogaster group have experienced positive selection on at least a subset of codons (q-value true-positive tests 77 ) (Supplementary Information section 11.1).…”
Section: Articlesmentioning
confidence: 99%